UNDERCUT AND TOOTH PROFILE MODIFICATION OF DOUBLE HELICAL PULLEY - GUO JianHua; LI JianBo; JIANG HongYuan; LI WenHua (Jixie qiangdu)
As for the smooth problems in the conjugate surface arising from hob tooth root and flank arc edge during the processing of new double helical synchronous belt’s pulley,the broken line generation mechanism at the conjugate tooth profile was investigated with spatial differential geometry and meshing theory. Through the undercut boundary curve characteristics analysis of the hob tooth profile surface,the parameter constraint conditions used to eliminate the pulley surface singularity was determined,and the eliminating profile singularity modification method by increasing the transition arc curve slope face on the hob tooth profile was proposed. Then the tooth profile hob practice model with undercutting constraints was built. The timing belt pulley’s hob tooth normal face profile parameters after modification was obtained based on coupling analysis of the modification pulley profile and double helical synchronous belt. The simulation shows that the pulley profile’s top curve after modification is smooth,it can reduce the abrasion during the meshing process and provide a useful modification method to improve the surface smoothness of the tooth belt.